Minat Masyarakat Kota Mataram Berwakaf Uang Yang Dimoderasi Oleh Religiusitas - Hidayat, Ali Akbar; Huzaini, Moh.; Ro'is, Ihsan (LPPM Institut Pendidikan Nusantara Global, 2024)
Waqf is one part of Islamic philanthropic instruments that can be used to support the economy. This research aims to analyze the factors that influence the interest of the people of Mataram city in cash waqf. This research is quantitative research with an associative approach. The data collection method uses a non-probability sampling with a purposive sampling approach. The research population is unknown, so sampling used the Lemeshow formula with a sample size of 130 respondents. The data used in this research is primary data taken using a questionnaire. This research uses data analysis tools with the Structure Equation Model (SEM) with the help of SmartPLS 3.0 software. The results of his research show that trust and subjective norms have a positive and significant effect on the interest of the people of Mataram city in giving cash waqf, while knowledge has no effect on the interest of the people of Mataram city in giving cash waqf. Meanwhile, trust, subjective norms and knowledge which are moderated by religiosity have no effect on the interest in cash waqf from the people of Mataram city.